The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.langmuir.5b03827
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Coffee-Ring Formation by Humidity Cycling: A Numerical Study

Abstract: Periodically switching between evaporation and condensation, or "humidity cycling", has potential for controlling the film shape that results from volatile droplets containing a nonvolatile material. It does not require adaptation of material properties nor the introduction of an external field to achieve a change in film shape. It was shown experimentally by Doi and coworkers [Kajiya et al. Langmuir 2010, 26, pp 10429-10432] that ring-shaped deposits can be removed through careful selection of the atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…When the residue was exposed to the solvent vapor for an optimum duration and dried again, its morphology changed from ring to disc. The numerical studies by Eales show that CRE is eliminated due to the refluidization of gelled regions during the condensation [142]. Refluidization brings back the spherical cap shape to minimize the surface energy.…”
Section: Humidity Cyclingmentioning
confidence: 99%
“…When the residue was exposed to the solvent vapor for an optimum duration and dried again, its morphology changed from ring to disc. The numerical studies by Eales show that CRE is eliminated due to the refluidization of gelled regions during the condensation [142]. Refluidization brings back the spherical cap shape to minimize the surface energy.…”
Section: Humidity Cyclingmentioning
confidence: 99%
“…For altering environmental conditions including humidity, temperature, and acoustic or electric fields, , complicated devices were needed to control the drying process. Eales and Routh showed that ring-shaped deposits could be removed through careful selection of the atmospheric conditions, and humidity cycling had potential for controlling the film shape of the volatile droplet. Deegan et al restricted evaporation from the edge of drop by covering the drop with a lid that had only a small hole over the center of the drop.…”
Section: Introductionmentioning
confidence: 99%